Dihydromyricetin preserves β-cell function in type 1 diabetes via PI3K/AKT-mediated metabolic reprogramming - Li, Jia; Li, Lijia; Lin, Tahui; Huang, Houtan; Ren, Jie; Yao, Jengyuan (Frontiers in Nutrition, 2025)
BackgroundFood-derived flavonoids are emerging as nutraceutical agents for glycemic control. Dihydromyricetin (DMY), the signature flavanonol of vine tea (Ampelopsis grossedentata), has long been consumed in South China, yet its antidiabetic potential remains underexplored.MethodsWe administered DMY (50 and 100 mg/kg/day, 12 days) to streptozotocin-induced type 1 diabetic mice. Fasting glycemia, lipid panels, and HOMA-β were evaluated 4 weeks after DMY administration. Untargeted UPLC-QTOF metabolomics combined with network pharmacology pinpointed pathway hubs, while experiments in INS-1 β-cells using the PI3K inhibitor LY294002 verified the pathway’s involvement.ResultsDMY reduced hyperglycemia, corrected dyslipidemia, and preserved islet architecture. Metabolomics indicated a shift toward a normal plasma profile, with the arachidonic acid, linoleic acid, and steroid hormone pathways being the most responsive. Six hub targets (PTGS2, IL6, AKT1, IL1B, BCL2, CASP3) mapped to eicosanoid signaling, apoptosis, and PI3K/AKT axis. Docking and cell assays confirmed direct binding and PI3K/AKT-dependent cytoprotection, evidenced by restored p-AKT, lowered ROS, and reduced caspase-3 cleavage.ConclusionDMY, a readily accessible food-derived bioactive compound, reprograms lipid-inflammatory metabolism and activates PI3K/AKT to safeguard β-cell viability, highlighting its nutraceutical promise for dietary management of autoimmune diabetes.